Injuries and Sports Medicine - Robert Wojda, Thomas; Stawicki, Stanislaw P. (IntechOpen, 2023)
Injuries and Sports Medicine deals with the diagnosis, treatment, and rehabilitation of common sport-related injuries, and will be valuable for any sports medicine physician as well as anyone interested in optimizing the performance of athletes, both elite level and recreational. The authors whose contributions make up this book are all experts in their respective fields and have a passion for sports medicine and for sharing new knowledge in this discipline with the rest of the world.